The Respone of Magrove Rhizophora Apiculuta Growth to Mud Stress Sidoarjo - Achmad Fauzan; Saiful Arifin (Universitas Muhammadiyah Sidoarjo, 2016)
This study aims to know the influence of the growing media Sidoarjo mud on the response of plants Rhizophora apiculuta on growth. This research was conducted in greenhouse of Faculty of Agriculture, University of Muhammadiyah Sidoarjo in April-June 2016. The experiment was arranged that a single factor by using a randomized block design that is repeated four times. The treatment consists of planting medium. without the Sidoarjo mud, mud Sidoarjo 10%, 20% Sidoarjo mud, mud Sidoarjo 30%, 40% and 50% mud Sidoarjo Sidoarjo mud. The variables measured were: plant height, stem diameter, leaf area, root length, fresh weight and dry weight stover. The whole observation data were analyzed using analysis of variance (ANOVA) followed by 5% HSD test to determine dif- ferences between treatments. The results showed differences in the concentration of the Sidoarjo mud negative effect on all variables observation. Sidoarjo mud concentration of 40% and 50% obtain a low response. While the concentration of 10% content of Sidoarjo mud showed a response not unlike the growth without Sidoarjo mud.